FEATURES OF THE FORMATION OF ANTI-CORRUPTION BEHAVIOR - Кулиев Ёркин Каримович (Journals Park Publishing, 2023)
The article examines anti-corruption behavior as a set of conscious actions to prevent and overcome corruption situations. It is noted that the basic grounds for the formation of anti-corruption behavior, as a rule, are the legal regulation and education of legal awareness in society. The main approaches to understanding the term "anti-corruption behavior", presented in the works of modern scientists, are considered.
Keywords: anti-corruption behavior, principles of anti-corruption behavior, formation of anti-corruption behavior, corruption, anti-corruption.